Innovative contributions towards therapeutic strategies for metastatic breast cancer treatment - Oliveira, Filipa (2023)
Breast cancer is the most frequently diagnosed cancer worldwide and is the leading cause of cancer-related death among women. Despite the vast therapeutic arsenal available to fight this heterogenous and complex disease, it still poses a challenge in the clinic. In fact, even though the extensive screening programs combined with improvements in the therapeutic management have been resulting in an increase of the median overall survival in women with metastatic breast cancer (MBC), this specific disease remains incurable. Moreover, as the incidence of MBC is increasing, more patients will die from this disease. The therapeutic approach for MBC relies on chemotherapy, which is associated with insufficient selectivity, that ultimately leads to drastic side-effects, and resistance to treatment. Additionally, while this type of therapy can be partially effective regarding metastases development in bones, soft tissue and viscera, MBC tends to spread to lungs, liver, bones and brain. Therefore, brain metastases represent a major clinical concern when treating and managing MBC, since the majority of the chemotherapeutic drugs present very poor penetration in the central nervous system (CNS) due to the impermeability of the blood-brain barrier (BBB). Therefore, there is the urgent need for more effective and innovative strategies for MBC treatment. In this work, our goal was to develop a new therapeutic strategy for the treatment of MBC that would selectively target breast cancer cells and interfere with the development of brain metastases. Considering the vast level of complexity of breast cancer, we decided that our approach would have to focus on molecular features that are widely found in cancer cells and tend to remain constant throughout time. Cancer cells exhibit a cell membrane with a net negative charge. Therefore, we decided to focus on the use of peptides with anticancer activity, because since these are generally cationic, their mode of action relies on the inevitable electrostatic interaction with cancer cells. In the first part of this work, we studied the anticancer activity of PvD1 – a plant defensin isolated from Phaseolus vulgaris, the common bean – and vCPP2319 – a cellpenetrating peptide (CPP) obtained from the capsid protein of the Torque teno douroucouli virus. The results showed that both peptides exhibited selective anticancer activity. The mode of action was also studied for both peptides and the results suggested that both peptides could potentially hinder the formation of metastases. Therefore, we concluded that these are promising molecules that can work as templates for the design of innovative approaches for MBC treatment. Nevertheless, peptides are still associated with some disadvantages as instability, immunogenicity, or limited ability to cross biological barriers such as the BBB. Hence, the second part of this work focused on the study of the interaction between extracellular vesicles (EVs) and vCPP2319. The goal was to use EVs as a potential drug delivery system (DDS) for vCPP2319. We isolated EVs from breast cancer cells MDA-MB-231 and studied the interaction between these and vCPP2319. As the results revealed the establishment of a strong interaction, we decided to test the ability of these EVs to deliver vCPP2319 across an in vitro model of the human BBB. The results revealed that, in contrast to what was observed for the peptide alone, vCPP2319 was able to transmigrate through the BBB model when combined with EVs. In line with these results, EVs did show the ability to transmigrate through the BBB, even without the peptide. In parallel with the present work, there were contributions that crossed roads with collaborations with other labs. One of those works was a literature review on the use of biophysical techniques to investigate the potential of bacteriocins as anticancer peptides (ACPs). Additionally, the anticancer activity of a peptide found in the venom glands of three different wasps, the protonectin (PTN), was studied. Aiming to explore alternative approaches for the use on EVs in breast cancer treatment, these vesicles were evaluated as a possible target for breast cancer treatment using the PvD1. Finally, there was also the participation in a project where several conditions were evaluated for the optimization of the production of EVs from mesenchymal stem cell cultures in bioreactors. All these works are in line with the main project that supports this thesis, adding on its contribution for new therapeutic strategies for metastatic breast cancer treatment. Overall, this thesis shows that ACPs are a very promising source of templates for the development of new molecules for MBC treatment and that EVs have the potential to work as a DDS with the ability to deliver its cargo across the BBB.